MALE MEIOSIS IN STRUCTURALLY HETEROZYGOUS AND HOMOZYGOUS TRERON, PHOENICOPTERA PHOENICOPTERA (LATHAM) (COLUMBIFORMES: AVES) FROM JHARKHAND - N. GUPTA; D. KAUL (The Bioscan, 2011)
Treron phoenicoptera phoenicoptera (Latham) is polymorphic for a pericentric inversion involving chromosome pair 2 in Jharkhand population. Analysis of meiotic stages was based on the study of ten male birds collected from Chotanagpur and Singhbhum areas of Jharkhand. Three distinct karyomorphs were observed for chromosome 2. Chromosome 2 has two to four chiasmata. In order to ascertain whether inversion heterozygotes leads to a significant reduction in chiasma frequency, the number of chiasmata were counted in bivalent 2 from fifty cells of each karyomorph. The observed and expected frequencies of bivalent 2 with less than three chiasmata and with three or more than three chiasmata have been calculated. A chi-square test was performed. The chi- square values are significant which indicate that there has been a decrease in chiasma frequency in the inversion heterozygotes.